2012
DOI: 10.1097/nan.0b013e31823bc8fd
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Alternative Workflow Model for Peripherally Inserted Central Catheter Placement

Abstract: Many challenges face vascular access nurses as technology improves and patients require more numerous and lengthy intravenous therapies. Nurses began placing peripherally inserted central catheters (PICCs) at the patient bedside in an effort to defray costly interventional radiology procedures and provide for patient comfort. In recent years, the numbers of PICC procedures have increased, and the procedure itself has become more technologically advanced. With these advances have come new logistical, environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Our data and previous studies appear to support the aforementioned hypotheses because the majority of CRT occurred within 3 weeks after insertion of PICCs. These data are consistent with results from a study of 1307 PICCs that suggested that a proper insertion technique decreased the incidence of thrombosis to 1.4 % [26]. Previously described risk factors for symptomatic CRT in cancer patients (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Our data and previous studies appear to support the aforementioned hypotheses because the majority of CRT occurred within 3 weeks after insertion of PICCs. These data are consistent with results from a study of 1307 PICCs that suggested that a proper insertion technique decreased the incidence of thrombosis to 1.4 % [26]. Previously described risk factors for symptomatic CRT in cancer patients (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…1 PICCs are versatile central venous catheters that enable tasks such as short-or long-term intravenous therapies, chemotherapy, and invasive hemodynamic monitoring. However, growing use of PICCs has also led to the realization that they are not without attendant risks.…”
mentioning
confidence: 99%
“…With these advances have come new logistical, environmental, and ergonomic challenges. 29 Due to the current financial circumstances in Greece, the effort to develop a new approach for the central venous access is quite difficult, and it would deteriorate if Greece does not have nongovernmental support as well as the personal efforts of health system professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Although the cost currently is still higher than that of the simple central catheterization, that cost can be significantly reduced by the use of fewer luxury sets and more limited ancillary equipment involved, making PICCs a cost-effective procedure. 22 …”
Section: Historymentioning
confidence: 97%